CURRENT ISSUES IN THE FIELD OF EDUCATION AND UPBRINGING - Nazarova Dilnoza; Rakhmonova Fariza Suxrobovna (Bright Mind Publishing, 2025)
The modern field of education and upbringing encompasses a wide range of pressing issues related to societal development, the rapid growth of scientific and technological advancements, and global changes. This article analyzes key problems in today’s education system, including the impact of information technology, the quality of the learning process, the balance between national and global educational principles, teacher qualification improvement, and ways to enhance education quality through innovative methods. The article also presents proposed solutions and recommendations for addressing these issues.
Keywords: Education, upbringing, pressing issues, information technology, education quality, innovation, teacher qualification.